Religious Reflectivity Against The Risks of Modernity: The “Real Medicine” Movement As A Reactive Alternative Medicine Movement To The Risk Society - Fatih Katınç; Abdurrahman Kurt (Darulfunun Ilahiyat)
This study examines the social reactions toward risks that emerged during the period referred to as late, advanced, or high modernity by Ulrich Beck and Anthony Giddens. These reactions transformed into new social movements with a certain organizational structure. Notably, certain movements have incorporated religious references as part of their approach. Among these movements are alternative medicine and the new age, which gained prominence in the latter part of the 20th century. In contrast to traditional movements, these contemporary movements embrace an alternative way of life, reacting against the potential risks posed by the modern way of life. This study focuses on the Aidin Salih School, an alternative medicine movement that has progressively expanded its area of influence. The most important reference sources of the members of this movement known as “Real Medicine” are Prophet’s Medicine. This concept serves as the “Angel of History” as an alternative to the modern way of life for the followers of Real Medicine. In this context, the aspiration is to reinvent the era of “Asr-ı Saadet, “ a period believed to have fully embraced the Prophet’s Medicine, as a form of retrotopia (an idealized past). The study aims to examine the motivating factors behind the “Real Medicine” movement as a representative of the alternative medicine movement and to scrutinize the social dynamics that shaped their adopted way of life.